Glutathione Pulse Therapy: Promote Spatiotemporal Delivery of Reduction‐Sensitive Nanoparticles at the "Cellular Level" and Synergize PD‐1 Blockade Therapy. Issue 27 (27th July 2022) - Dong, Songtao; Zhang, Yuan; Guo, Xiangnan; Zhang, Chuang; Wang, Zhaomeng; Yu, Jiang; Liu, Yubo; Li, Chang; Hu, Yuting; Sun, Bingjun; Sun, Mengchi; Zhang, Haotian; et al.
Abstract: Spatiotemporal delivery of nanoparticles (NPs) at the "cellular level" is critical for nanomedicine, which is expected to deliver as much cytotoxic drug into cancer cells as possible when NPs accumulate in tumors. However, macrophages and cancer‐associated fibroblasts (CAFs) that are present within tumors limit the efficiency of spatiotemporal delivery. To overcome this limitation, glutathion pulse therapy is designed to promote reduction‐sensitive Larotaxel (LTX) prodrug NPs to escape the phagocytosis of macrophages and penetrate through the stromal barrier established by CAFs in the murine triple negative breast cancer model. This therapy improves the penetration of NPs in tumor tissues as well as the accumulation of LTX in cancer cells, and remodels the immunosuppressive microenvironment to synergize PD‐1 blockade therapy. More importantly, a method is established that can directly observe the biodistribution of NPs between different cells in vivo to accurately quantify the target drugs accumulated in these cells, thereby advancing the spatiotemporal delivery research of NPs at the "cellular level." Abstract : Schematic diagram of glutathione (GSH) pulse therapy is shown. GSH pre‐injections remodel the tumor stromal and immunosuppressive microenvironment, which enhance the penetration of nanoparticles (NPs) and synergize the PD‐1 inhibitor therapy. Moreover, the GSH injection at the maximum LTX‐SS‐CA NPs accumulation point significantly promotes the cytotoxic drug Larotaxel to be delivered into cancer cells and reflects remarkable antitumor outcomes.